ANALISIS PEMEROLEHAN BAHASA ANAK BILINGUAL USIA 8 TAHUN (STUDI KASUS B1 BAHASA BATAK TOBA DAN B2 BAHASA INDONESIA) - Tia Aprinisa Simanjuntak; Eka Putri Saptari Wulan; Gresia Natasia Br Purba (Jurnal PENEROKA, 2026)
This study aims to analyze language acquisition in 8-year-old bilingual children with Toba Batak as their first language (B1) and Indonesian as their second language (B2). The study used a qualitative approach with a case study method on a child named Refael Simanjuntak who actively uses both languages ??in everyday life. Research data were obtained through observation, interviews, documentation, and listening and note-taking techniques. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Toba Batak language is acquired naturally through interactions within the family and community environment, making it the dominant language used by the subject. Meanwhile, Indonesian is acquired through the school environment and broader social interactions. The subject demonstrated good language skills in the aspects of phonology, morphology, syntax, and vocabulary in both languages. In addition, code-mixing and code-switching phenomena were found, demonstrating the subject's ability to adjust language use based on the situation and the interlocutor. The findings of this study indicate that the family and school environment have an important role in supporting the development of children's bilingualism.  Thus, the subjects' acquisition of Toba Batak and Indonesian occurred optimally and reflects the development of good bilingual skills. These findings also indicate that using two languages ??from an early age does not hinder children's language development but can instead increase their communication flexibility and ability to choose the appropriate language for the social context they encounter.